Increased HIV Risk Associated with Criminal Justice Involvement among Men on Methadone - Epperson, Matthew (2007)
This paper examines the relationship between HIV risk and criminal justice involvement among a random sample of 356 men enrolled in methadone maintenance treatment programs in New York City. Bivariate and logistic regression analyses were performed to estimate the associations between measures of criminal justice involvement and participant HIV risk, controlling for socio-demographic variables. A lifetime history of incarceration was significantly associated with being HIV positive (Adjusted OR = 5.08). Recent arrest was associated with unprotected vaginal sex and having multiple female sexual partners. Sex trading was associated with both arrest and incarceration, and the strongest association was found between selling sex and recent incarceration (Adjusted OR = 5.69). Results suggest that recent criminal justice involvement among men with substance abuse histories is associated with increased HIV risk behaviors. Findings underscore the need for targeted HIV prevention efforts for men on methadone with a recent history of arrest or incarceration.